Prognostic Impact of Parity in 493 Uterine Sarcoma Patients. Issue 6 (1st July 2009) - Albrektsen, Grethe; Heuch, Ivar; Wik, Elisabeth; Salvesen, Helga B.
Abstract : Introduction: Nulliparity has been found to negatively affect prognosis among endometrial cancer patients. Few previous studies have examined the prognostic impact of parity in patients with uterine sarcomas. Methods: In the present nationwide, register-based study in Norway, we explore whether parity influences survival among 493 women diagnosed with malignant uterine sarcomas. Hazard ratios for total mortality were calculated in Cox proportional hazard regression analyses. Results: The 5-year Kaplan-Meier survival rates for the 126 endometrial stromal sarcoma (ESS) patients, 249 leiomyosarcoma (LS) patients, and 118 carcinosarcoma (CS) patients were 74%, 68%, and 55%, respectively, but varied considerably by age at diagnosis and clinical stage. In the univariate analyses, nulliparous women had poorer prognosis than parous women among CS patients ( P = 0.071, log-rank test) and ESS patients ( P = 0.15). In analyses adjusted for clinical stage and age at diagnosis, nulliparity was associated with a worse outcome in ESS patients only (hazard ratio, 0.50; 95% confidence interval, 0.22-1.12; parous vs nulliparous women); a trend with increasing number of births was also observed, of borderline significance ( P = 0.058). No independent prognostic impact of parity was found in LS or CS patients. However, a considerably higher proportion of nulliparous than parous CS patients was diagnosed with advanced-stage disease ( P = 0.003). Conclusion: Nulliparity seems to be associated with poorer prognosis in ESS patients; no independent prognostic impact of parity was seen among LS or CS patients. Further knowledge on underlying biological mechanisms may be valuable for improved treatment.